The relationship between Islamic theology and poetry - Nasufović Sead (Kom: Časopis za Religijske Nauke)
The relationship between religion and poetry is a complex and dynamic subject that requires consideration of many factors, including theological, cultural, historical, and personal contexts. The relationship between these two spheres throughout history was motivated differently, which is why various questions were raised on the theoretical level, such as: is literature a part of theological discourse and/or is theology a part of literary discourse? It is possible that literature and theology intertwine and influence each other in different ways, but accepting their definitive affiliation with each other remains a matter of theoretical debate. In the Eurocentric circle, the most pronounced relationship between theology and literature continues intensively in medieval literature, when the Bible becomes the paradigm according to which all other forms of human and cultural activity are determined, while in the Balkans (from the end of the 15th to the end of the 19th century) the Qur'an will also be literature of the oriental-Islamic circle. Based on several shorter theses that we presented from the Islamic theological aspect, we concluded that Islam allows, even praises, poetry, but does not give it complete autonomy. These restrictions are depicted in the form of the necessary respect and adherence to the norms of Islamic belief and religious laws, which the poet must not renounce, nor express himself poetically in terms of content, while the form of the poem itself is left to the poet's full freedom of choice. The beginning of the 21st century was marked by several literary-critical works that point to the problem of naming and classifying Islamic religious poetry in our speaking area, which indicates the necessity of forming the principles of Islamic theological aesthetics and literary theory.